2012
DOI: 10.1242/dev.070151
|View full text |Cite
|
Sign up to set email alerts
|

miR-200c regulates FGFR-dependent epithelial proliferation via Vldlr during submandibular gland branching morphogenesis

Abstract: SUMMARYThe regulation of epithelial proliferation during organ morphogenesis is crucial for normal development, as dysregulation is associated with tumor formation. Non-coding microRNAs (miRNAs), such as miR-200c, are post-transcriptional regulators of genes involved in cancer. However, the role of miR-200c during normal development is unknown. We screened miRNAs expressed in the mouse developing submandibular gland (SMG) and found that miR-200c accumulates in the epithelial end buds. Using both lossand gain-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 123 publications
4
54
0
Order By: Relevance
“…The capacity of reelin to regulate cell proliferation, migration, and differentiation agrees with observations made in neural [29][30][31] and non-neural tissues, such as submandibular 32 and mammary gland. 33 However, inhibition of cell migration in primary cultures of mammary epithelial cells 33 and of apoptosis in embryonic carcinoma cells 34 by exogenous reelin have also been reported.…”
Section: -21supporting
confidence: 86%
See 1 more Smart Citation
“…The capacity of reelin to regulate cell proliferation, migration, and differentiation agrees with observations made in neural [29][30][31] and non-neural tissues, such as submandibular 32 and mammary gland. 33 However, inhibition of cell migration in primary cultures of mammary epithelial cells 33 and of apoptosis in embryonic carcinoma cells 34 by exogenous reelin have also been reported.…”
Section: -21supporting
confidence: 86%
“…50 (4) The absence of reelin reduces the intestinal expression of a large number of genes that code for proteins involved in the intestinal immune response, inflammation, and cancer processes. 17 As several reports have proposed a role for reelin in tissue repair in both, neural 31,[51][52][53] and nonneural tissues, 32,51,54 its involvement in the activation of cell proliferation and migration during the mucosal regenerative response triggered by injury could not be discarded.…”
Section: -21mentioning
confidence: 99%
“…3). In the context of developmental program, miR-200c has been found to accumulate in epithelial buds in developing submandibular glands and control FGFR-mediated epithelial proliferation by targeting vldlr and its ligand reelin which regulate FGFR signaling in these cells [90]. Furthermore, miR-200c-mediated activation of BMP signaling via upregulation of amelogenin and E-cadherin and via downregulation of noggins triggers tooth development and renewal through dental epithelial cell differentiation in mice [91].…”
Section: Mir-200c Regulation Of Signaling Pathwaysmentioning
confidence: 99%
“…Together, these molecular and genetic studies have revealed that branching morphogenesis appears to be controlled by a conserved set of molecules, including fibroblast growth factors (FGFs), which signal through the mitogen-activated protein kinase (MAPK) cascade. Recent studies have also indicated a role for miRNAs in branching morphogenesis of the lung, kidney, salivary gland and vasculature (Biyashev et al, 2012;Chu et al, 2014;Hayashi et al, 2011;Jiang et al, 2013;Mujahid et al, 2013;Rebustini et al, 2012;Yu, 2014).…”
Section: Introductionmentioning
confidence: 99%